2017
DOI: 10.1016/s1473-3099(17)30123-8
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis is changing

Abstract: is Changing This March, Public Health England will officially launch a routine whole-genome sequencing service for mycobacterial infections, becoming the first national administration in the world to do so. The implications are profound with many of the methods that have become commonplace around the world being replaced. From now on, when mycobacterial cultures are referred to reference facilities, comprehensive whole-genome sequencing-based reports will be returned within 5-7 days. Reports will detail mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 7 publications
0
59
0
Order By: Relevance
“…This may cause a small improvement in cost-effectiveness, as we would now expect a higher yield of LTBI per case, as more contacts will be tested for LTBI, provided it is not accompanied by lower rates of PT enrolment and completion. The introduction in 2017 of whole genome sequencing (WGS) in the UK39 may also affect our conclusions. While a study of the current strain typing service found no impact on contact tracing,23 it is plausible that faster turnaround times and improved targeting available with WGS may affect contact tracing yields.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause a small improvement in cost-effectiveness, as we would now expect a higher yield of LTBI per case, as more contacts will be tested for LTBI, provided it is not accompanied by lower rates of PT enrolment and completion. The introduction in 2017 of whole genome sequencing (WGS) in the UK39 may also affect our conclusions. While a study of the current strain typing service found no impact on contact tracing,23 it is plausible that faster turnaround times and improved targeting available with WGS may affect contact tracing yields.…”
Section: Discussionmentioning
confidence: 99%
“…All mycobacterial positive cultures sent to the PHE reference laboratory undergo WGS, with reports returned to clinicians within five to seven days detailing mycobacterial species, and predicting drug susceptibility and genetic relatedness for the Mycobacterium tuberculosis complex. 14 It is anticipated that this will have profound impacts upon treatment and control of TB in the UK, including individually tailored anti-tuberculosis therapy according to the susceptibility of the specific mycobacterium causing infection. 15…”
Section: Molecular Diagnostics For Detection Of Mycobacteriamentioning
confidence: 99%
“…Its utility increases with the proportion of genome obtained; from detection, to speciation and antimicrobial resistance prediction, to phylogenetic and evolutionary insights. This allows whole genome sequencing (WGS) to out-perform other rapid molecular methods (such as GeneXpert MTB/RIF, Cepheid, Solna, Sweden) due to susceptibility predictions to multiple drugs, and its combination with classical epidemiological methods which informs transmission (58).…”
Section: Introductionmentioning
confidence: 99%
“…WGS of MTB from early positive cultures offers markedly faster results than traditional culture-based methods which take ≤80 days. The national implementation of Illumina sequencing of Mycobacteria from early positive cultures in England provides WGS in three to four weeks, together with antimicrobial resistance predictions (5, 9). Time to WGS could be reduced further if routine sequencing could be performed direct-from-sample.…”
Section: Introductionmentioning
confidence: 99%